A Sustainability Perspective Analysis of the Donggi-Senoro Gas Refinery Development - Gati, Rindri Andewi; Prasetyanti, Retnayu; Posumah, Risky Yustiani (KnE Social Sciences, 2022)
Mining and the production of oil and gas are two industries that contribute significantly to development. The impact of the Donggi-Senoro gas refinery development in Banggai Regency, Central Sulawesi on sustainability was assessed using a qualitative research framework. Data were gathered through direct interviews and field observations, which were supplemented by secondary data in the form of regional planning and evaluation documents. According to the findings, the oil and gas industry contributed significantly to regional income growth and economic development in Banggai Regency. The oil and gas industry’s growing contribution to regional spending is expected to support macro development in Banggai Regency, particularly community-oriented economic development, despite its low proportion in comparison to the agricultural and plantation sectors, as well as the marine sector. Since 2015, this multilevel partnership has been at the forefront of building public facilities, infrastructure, and social projects as a form of corporate social responsibility (CSR). However, the study concluded that pursuing long-term gains is hampered in general. The construction of Donggi-Senoro has benefited only a few members of the community. The ‘trickle-down effect’ was stifled due to a lack of long-term CSR monitoring and the Local Government’s political commitment to forming an integral and long-term public-private partnership. Capacity building, a regional economic development roadmap based on an impact analysis, and a CSR-based empowerment program were among the recommendations made in this study. Keywords: development, sustainability, public-private-partnership